Antonio de Nebrija (1444-1522), passion for knowledge - Regueiro Rodríguez, María Luisa (Razón y fe, 2022)
The article includes the evocation of Antonio de Nebrija, introducer of Renaissance Humanism in Spain, on the 500th anniversary of his death in 1522. His passion for knowledge and the plurality of cultural, scientific and religious interests that manifest in the richness of his legacy as teacher, Latinist, grammarian, pedagogue, lexicographer, royal chronicler, historian, editor and biblical are highlighted exegete.
Keywords: Grammar; renaissance; humanism; polymathy